CURRÍCULOS NOS COTIDIANOS: VIVÊNCIAS CORPORAIS NA PERSPECTIVA DOS JOGOS COOPERATIVOS PARA ALUNOS DO PROEJA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This paper is part of our doctoral research, which is in progress, and it dialogues with the inventiveness and agency of the subject practitioners who lead and develop the curriculum on knowledge-doings networks. Our methodological path was built from the cartographic method and by research on quotidian. We have problematized the production of subjectivities in educational processes in Physical Education classes for Young and Adult Education (Proeja/Ifes) motivated by the urgent need of creating more powerful educational orders, which encourage formation and self care, recognizing the other as a legitimate other in interaction. From the perspective of cooperative games, through bodily experiences, we aimed at demystifying the need of encouraging competition – which is so valued on the traditional model of Physical Education – and at proposing cooperation as an alternative way to ethics and aesthetics of existence – production of a pretty life and, thus, of a more competent and less competitive society.
Keywords: Proeja; Ifes; Quotidian; Physical Education; Cooperative Games